2016
DOI: 10.1371/journal.pgen.1006531
|View full text |Cite
|
Sign up to set email alerts
|

A Differentiation Transcription Factor Establishes Muscle-Specific Proteostasis in Caenorhabditis elegans

Abstract: Safeguarding the proteome is central to the health of the cell. In multi-cellular organisms, the composition of the proteome, and by extension, protein-folding requirements, varies between cells. In agreement, chaperone network composition differs between tissues. Here, we ask how chaperone expression is regulated in a cell type-specific manner and whether cellular differentiation affects chaperone expression. Our bioinformatics analyses show that the myogenic transcription factor HLH-1 (MyoD) can bind to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 89 publications
5
43
0
Order By: Relevance
“…Variable chaperones, in contrast, might be upregulated by tissue-specific transcription factors. In support, the main muscle differentiation transcription factor, MYOD1 (HLH-1 in C. elegans), was shown to drive the expression of chaperones in C2C12 mouse myoblast and C. elegans muscles (19,60,61).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Variable chaperones, in contrast, might be upregulated by tissue-specific transcription factors. In support, the main muscle differentiation transcription factor, MYOD1 (HLH-1 in C. elegans), was shown to drive the expression of chaperones in C2C12 mouse myoblast and C. elegans muscles (19,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…We further tested the functional conservation of muscle chaperones by comparing between human and the evolutionary distant multicellular organism Caenorhabditis elegans. We used a set of C. elegans chaperones that were enriched in muscle (19), and compared them to orthologous chaperones that were upregulated in human muscle (see Methods). We found that the two subsets overlapped significantly (p=0.0009, Fisher exact test, Fig.…”
Section: A Conserved Chaperone Expression Pattern In Musclementioning
confidence: 99%
See 2 more Smart Citations
“…The artificial over-expression of Hsp90 in C. elegans embryos was recently shown to cause the massive degradation of muscle proteins (Bar-Lavan, Shemesh et al 2016), indicating that in the cytosol of stressed eukaryotic cells, Hsp90 might also mediate the specific degradation of misfolding proteins that escaped the action of other members of the chaperone network. It will now be interesting to address which are the particular protein partners in bacteria that mediate the interaction of Hsp90 and Hsp70 clients with the cellular proteases and further address the possibility that also in eukaryotes, Hsp90s could mediate the degradation by proteasome of Hsp70-clients that failed proper folding under stress or owing to mutations.…”
Section: Discussionmentioning
confidence: 99%